2018
DOI: 10.1021/acs.iecr.8b01680
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sensor Location in Chemical Plants Using the Estimation of Distribution Algorithms

Abstract: The optimal selection of sensor structures improves the knowledge of the current plant state, which is a central issue for the decision-making process. Instrumentation design is a challenging optimization problem that involves a huge amount of binary variables that represent the possible sensor locations. In this work, the limitations of the current design strategies are discussed, and they support the application of evolutionary solution methods. Among them, the estimation of distribution algorithms (EDAs) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this section, we compare the behavior of the best algorithmic variants of HSA versus other well-known algorithm found in the literature for solving these SNDP case studies, in order to answer the RQ3. In this sense PBIL SOTS, introduced by Carnero et al [5], has recently reported results for these cases.…”
Section: Comparison Of Hsa Variants Against a Literature Approachmentioning
confidence: 80%
See 3 more Smart Citations
“…In this section, we compare the behavior of the best algorithmic variants of HSA versus other well-known algorithm found in the literature for solving these SNDP case studies, in order to answer the RQ3. In this sense PBIL SOTS, introduced by Carnero et al [5], has recently reported results for these cases.…”
Section: Comparison Of Hsa Variants Against a Literature Approachmentioning
confidence: 80%
“…Exponential Scheme. The exponential cooling scheme produces the temperature decay by applying the Eq (4), where the constant α k < 1 is calculated as presented in the Eq (5). This schedule quickly cools the temperature reducing the required time and iterations to converge to a good solution.…”
Section: Cooling Processmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, all of the evaluated MIP methods, i.e., MILP, MIQP, MT-MIQP, MIQP-MT, and MIQP-NT, were applied to a case used by Carnero et al, 40 which involves 47 units connected with 82 streams. The detailed information of the tested case is taken from https://www.ing.unrc.edu.ar/ archivos/sndp_cases.doc and can also be seen in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%